Association of Plasma Progesterone and Pregnancy Associated Glycoproteins in Post-Insemination Conceived and Non-conceived Gir Cows and Jaffarabadi Buffaloes Detected by BovEasy Rapid PD Kits - Devmurari, Yash J; Vala, Karshan B; Parikh, Suryakant S; Vijyeta, Hardipsinh P; Dhami, Arjan J (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This research focused on healthy 75 Gir cows and 75 Jaffarabadi buffaloes, 60-65 days postpartum that were inseminated during the detected estrus and did not return to repeat estrus till day 22 post-AI. They underwent pregnancy diagnosis by plasma progesterone on Days 21, 28, 36, and 45; pregnancy-associated glycoprotein (PAG) on Days 28, and 36 post-AI; PAG based BovEasy rapid PD kits on day 28 and 32, and per rectal confirmation on day 45 post-AI. The study assessed and compared conception rates, and the levels of progesterone and PAG by RIA and ELISA, respectively, in conceived and non-conceived animals. The BovEasy bovine rapid PD kits showed very high (100%) accuracy, sensitivity, and specificity in detecting early pregnancy. In all 37 cows & 25 buffaloes were found pregnant by day 32 with PD kits, and the overall actual pregnancy rate at day 45 was 36.7% (55/150,) indicating 4.7% (7/150) embryonic mortality. There was a significant increase in plasma P4 levels in both cows and buffaloes from Day 21 (2.92 ± 0.27 and 2.40 ± 0.23 ng/ mL) to Day 45 (7.61 ± 0.71 and 5.75 ± 0.67 ng/mL) and PAG from day 28 (5.27 ± 0.87 and 4.48 ± 0.9 ng/mL) to day 36 (9.93 ± 1.63 and 6.96 ± 1.39 ng/mL) in conceived animals, while in non-conceived animals the P4 was unstable, with significant fluctuations over the days measured, but PAG values always remained below 1 ng/mL. In both the species, a highly significant differences (p<0.000) in P4 and PAG levels were noticed between pregnant and non-pregnant animals on all test days with strong positive correlations (p<0.01) between P4 and PAG levels on all days, but in non-pregnant animals the changes in PAG were not strongly related to changes in progesterone. Thus, BovEasy rapid pregnancy kit or plasma PAG estimates can serve as effective markers for early pregnancy detection in bovines as it reflects the trophoblast activity and presence of viable fetus in uterus.